Análisis psicosocial de la relación comercial entre vendedores informales y sus consumidores: un estudio en las ciudades de Neiva y Cartagena sobre el comercio informal de café (2008)
The primary objective of this research was to describe the social relationships established in 60 informal coffee sellers and their customers in the cities of Neiva and Cartagena (Colombia), taking as a base the Michael Argyle's Social Relations Theory (1992). Data were obtained through qualitative and quantitative approaches, under observations and semi-structured interviews and surveys techniques. Results indicate that the analysis units proposed in the Social Relations Theory can be used to understand the relationship among informal coffee vendors and their customers, taking into account that in each meeting or interaction among them there is a) the effective presence of two actors that know each other; b) a frequency and a permanence in the interaction that can be registered and quantified; c) an exchange activity that reports a result for each one of the actors; and d) a course in such interaction. Key words: informal commerce, coffee, social relations, informal vendors, customers.